Film thickness and traction curves of wind turbine gear oils. (June 2015) - Fernandes, Carlos M.C.G.; Marques, Pedro M.T.; Martins, Ramiro C.; Seabra, Jorge H.O.
Abstract: The film thickness and the traction curves of four fully formulated wind turbine gear oils were measured on a ball-on-disc device. All oils have the same viscosity grade (ISO VG 320) and different formulations: ester, mineral, PAO and mineral+PAMA. Film thickness and traction coefficient results will be presented. The film thickness measurements were compared with predictions using film thickness equations from the literature. Abstract : Highlights: Four wind turbine gear oils were selected. Film thickness measurements at different temperatures. Torque loss was measured for a type C40 FZG gears. Traction coefficient and Stribeck curves.